Relocation of the distribution center of a motor oil producer reducing its storage capacity: A case study. (November 2019) - González-Hernández, Isidro Jesús; Martínez-Flores, José Luis; Sánchez-Partida, Diana; Gibaja-Romero, Damián Emilio
Enterprises face the challenge of identifying, following, and controlling the performance of their processes in the whole supply chain (SC) to guarantee an adequate level of service to the client. Since the delivery of orders on time has a direct impact in the client's satisfaction, the managers of the SC face the challenge of choosing the best location, number, and capacity of the facilities to deliver the client's orders on time. In this paper, we address a facility relocation problem. A motor oil manufacturing company currently has a distribution center (DC) with 17, 800 storage locations and 20 docks for loading and unloading, operated traditionally, and it wishes to relocate the DC to a smaller one of 10, 800 storage locations operated in an automated way. However, they do not have the certainty that the relocated DC will support the distribution logistics operation to deliver the clients' orders on time. In this research, we make a feasibility analysis of the distribution logistics operation when relocating the DC through a simulation model. For that, it was essential to analyze the main storage and distribution processes of the new DC. The main contribution of this work is the development of a simulation model that can be used to analyze the feasibility of relocating a warehouse or DC to a specific location; the model establishes the main key performance indicators that must be evaluated in the simulation. The results of the simulation show that it is feasible to implement the relocation.